Diagnosis dan Tata Laksana Graves’ Disease: Tinjauan Pustaka - Eric Ricardo Yonatan (Cermin Dunia Kedokteran, 2025)
Graves’ disease is the primary cause (60%-80%) of hyperthyroidism. The risk factors include genetic, environmental, and immunological aspects, with a higher prevalence in women. The diagnosis is based on medical history and physical examination, supported by Wayne index, as well as appropriate diagnostic tests including thyroid function tests, antibody testing, thyroid scan, or color-doppler ultrasonography. Treatment options include anti-thyroid medication, radioactive iodine treatment (RAI), and surgery. Complications include Graves’ ophthalmopathy, thyroid dermopathy, cardiovascular effects, and thyroid crisis. The prognosis depends on the likelihood of remission and relapse, with remission being more common in adults than in children.